Human Anatomy & Psycholog - David Le Vay (Teach yourself books, 2003)
Teach Yourself Human Anatomy and Physiology is the ideal introduction to the structure and function of the human body. The composition and properties of body tissues are fully described, together with the anatomy of the various body systems and their component tissues. The second part of the book focuses on physiology and related biochemical and biophysical processes. Extensively illustrated, Teach Yourself Human Anatomy and Physiology covers: - modern methods of investigation of structure and function - relevant aspects of modern genetics - aspects relating to physical training and sports injuries - environmental and evolutionary considerations - physiological aspects of AIDS.